Control de bienes del departamento de bodega del Cuerpo de Bomberos de Vinces - Cervantes Vera, Kelly Alexandra (2017)
The Fire Department is an institution that began operations in the City of Vinces on August 18, 1882, dedicated to the care and protection of the Vinceña population in all types of events, whether these forest fires, structural, rescue in traffic accidents , among others, making it possible to serve the citizens the necessary help, since today there are different natural cases that affect the environment and society. It is constituted by two sections, in operative area and the administrative area, the operative area is related to the personnel that carry out emergency activities and those volunteers who are willing to serve, and the administrative area is directed to everything related to the managements of the institution indicated, this unit is conformed by several departments as they are: Headquarters, Treasury, Secretary and Warehouse, in this last department is where the investigation of this case study is centered. In Ecuador the Fire Departments